Savings As Part of Thermal Modernization Activities as An Element of Environmental Protection Activities - Selected Aspects - Adam WYSZOMIRSKI (Communications of International Proceedings, 2023)
The aim of the work is to show the impact of financial support on the implementation of thermal modernization activities in Poland. The test was to demonstrate that effective management of aid funds will significantly influence the implementation of thermal modernization projects. The results obtained from the conducted research indicate that in the examined period (1999 - 2022) 51,254 applications were submitted in Poland for a total amount paid of PLN 2,522,188 thousand. It is worth noting that the beneficiaries of these funds were housing communities and cooperatives, natural persons, local government units and social housing societies. However, the most important effect achieved thanks to the implementation of thermal modernization activities resulting from the support obtained was the improvement of energy efficiency (savings in energy costs of almost PLN 1.2 billion).
Keywords: thermal modernization; financing; energy efficiency